The Development of POE-based (Predict, Observe, and Explain) E-Student Worksheet for Eleventh-Grade Plant Histology Subject - Wulandari, Rina Wulan; Nofina, Mufida (Biosfer: Jurnal Tadris Biologi, 2022)
This research developed electronic student worksheet (e-student worksheet) based on POE (Predict, Observe, and Explain) using the Liveworksheets feature. The research method was R&D (Research and Development) with a 4-D model, namely define, design, develop, and disseminate. There were three data collection techniques in this research, namely interview, questionnaire, and N-gain from the pretest and posttest scores. The analyzed data using qualitative descriptive analysis. The results showed that (1) the average percentage of e-student worksheet feasibility obtained was 92.90% with material expert validators of 94.23%, media expert validators of 88.23%, and practitioner validators of 96.25%. Therefore, the POE-based e-student worksheet can be used with a very valid or very feasible category. (2) The percentage obtained from student responses was 85% with a very good category. (3) The N-Gain value obtained was 0.39 with a medium category. Thus, the development of e-student worksheet based on POE (Predict, Observe, and Explain) on plant tissue material for the eleventh-grade students can be used with a very feasible category.ABSTRAK: Penelitian ini bertujuan mengembangkan lembar kerja siswa elektronik (e-student worksheet) berbasis POE (Predict, Observe, and Explain) dengan menggunakan fitur Liveworksheets. Metode penelitian yang digunakan adalah R&D (Research and Development) dengan model 4-D, yaitu define, design, develop, dan distribute. Ada tiga teknik pengumpulan data dalam penelitian ini, yaitu wawancara, angket, dan N-gain dari nilai pretest dan posttest. Teknik analisis yang digunakan deskriptif kualitatif. Hasil penelitian menunjukkan bahwa (1) rata-rata persentase kelayakan LKS yang diperoleh adalah 92,90% dengan validator ahli materi 94,23%, validator ahli media 88,23%, dan validator praktisi 96,25%. Oleh karena itu, LKS e-student berbasis POE dapat digunakan dengan kategori sangat valid atau sangat layak. (2) Persentase yang diperoleh dari respon siswa sebesar 85% dengan kategori sangat baik. (3) Nilai N-Gain yang diperoleh sebesar 0,39 dengan kategori sedang. Dengan demikian, pengembangan LKS berbasis POE (Predict, Observe, and Explain) pada materi jaringan tumbuhan untuk siswa kelas XI dapat digunakan dengan kategori sangat layak.